Analysis of Flood Prone Areas in Melawi Sub Watershed Using Geographic Information System - Candra, Diki; Soeryamassoeka, Stefanus Barlian; Gunarto, Danang (Fakultas Teknik Universitas Tanjungpura, 2024)
Floods are a common natural disaster in West Kalimantan, including in the Melawi Sub-Watershed, causing infrastructure damage, economic losses, and even fatalities. One of the leading causes of flooding is the destruction of catchment areas and significant land cover changes. The Melawi sub-Watershed has numerous mining areas, many of which are illegal, leading to upstream erosion and downstream sedimentation. Therefore, mapping flood-prone areas in the Melawi Sub-Watershed is crucial for disaster mitigation and preventing environmental damage that affects community activities. This study aims to map flood-prone areas in the Melawi Sub-Watershed using a Geographic Information System (GIS) and analyze the factors influencing flood susceptibility. The data include land cover, soil type, slope, elevation, rainfall, river buffers, and historical flood inundation. The overlay method was used to create the flood susceptibility map, involving scoring, weighting, and overlaying. The most dominant flood susceptibility level in the Melawi Sub-Watershed is moderate, covering 48.21% of the total area, mainly in the downstream regions. Meanwhile, the low flood susceptibility category is more prevalent upstream, with higher topography and land cover well-preserved.